Alteração no zoneamento rural e de chácaras urbanas: estudo de caso da revisão do plano diretor de Sorocaba de 2014, sob a ótica da gestão das águas. - Correa, Denise Martins (2025)
The preservation and qualification of rural areas and small farms (chácaras) is of utmost importance for the proper management of water resources, avoiding or minimizing problems caused by water scarcity or excess, which tend to worsen with climate change. Urban policy in Brazil, established in 1988 by the Federal Constitution and regulated in 2001 by the City Statute, provides instruments to guide land use and occupation in municipalities and is based on the municipal master plan for urban development. The present study aims to investigate the change in zoning in rural areas and urban farms in the municipality of Sorocaba, following the review of the municipal master plan in 2014. The methodology was divided into three stages, according to the specific objectives: a) to identify, quantify, and qualify the altered areas through comparative analysis between the zoning and environmental macrozoning maps from the 2007 and 2014 revisions, using QGIS and Excel software; b) to investigate the criteria for the changes through documentary and comparative analysis between Municipal Laws 8,181/2007 and 11,022/2014, qualitative analysis of the administrative process of the 2014 review, and analysis of the local media by searching for the descriptor “master plan” in the digital collection of Jornal Cruzeiro do Sul from 2014; and c) to investigate changes in land use and occupation that occurred in the territory through the analysis of historical maps on Google Earth. A significant amount of rural and urban farms areas was found to have been altered (approximately 15% of the municipality’s area), most of which were changed to zoning that allows the construction of low-income housing lots, even though a large part is classified in the environmental macrozoning as areas with major restrictions on urbanization. No justifications were found in the law for the changes, only some arguments in the media, and there have been few transformations in the territory even after ten years. It was concluded that the changes were proposed and approved without justification or technical reasoning, that the criteria were limited to meeting the real estate market, and that the changes have not yet caused a major impact on the territory, but their destructive potential is latent.